1980
DOI: 10.1111/j.1651-2227.1980.tb07051.x
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF MECHANICAL VENTILATION IN NEWBORN INFANTS: I. Techniques and survival rates

Abstract: The short-term outcome with survival rate, causes of death and neonatal complications in a 6-year material comprising 253 infants treated with intermittent positive pressure ventilation (IPPV) in the neonatal period has been analyzed in relation to different primary disorders necessitating IPPV treatment. The total survival rate was 53%. For the different diagnoses the survival rates were: hyaline membrane disease (HMD) 41%, apnoea repetens of immaturity 85%, severe birth asphyxia 46% and septicemia 59%. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…If the work of breathing exceeds the working capacity of the respiratory muscles and respiratory failure occurs, artificial ventilation will become necessary [17]. Quality of survival in these babies may depend on the complications as well as on the limitations of artificial ventilation [18][19][20][21][22]. We have found a significant correla- tion between the radiological score and the respiratory compliance (R~=-0.5776; p<0.001; Fig.2).…”
Section: Discussionmentioning
confidence: 82%
“…If the work of breathing exceeds the working capacity of the respiratory muscles and respiratory failure occurs, artificial ventilation will become necessary [17]. Quality of survival in these babies may depend on the complications as well as on the limitations of artificial ventilation [18][19][20][21][22]. We have found a significant correla- tion between the radiological score and the respiratory compliance (R~=-0.5776; p<0.001; Fig.2).…”
Section: Discussionmentioning
confidence: 82%
“…After the initial hour when a standardized program was applied all infants took part in the normal routine care in the Neonatal Intensive Care Unit (NICU) [15,27]. Besides the study group of preterm infants a control group of 13 term vaginally born infants without risk factors in pregnancy or complications in delivery was followed with similar examinations.…”
Section: Methodsmentioning
confidence: 99%
“…In Lindroth's study, they showed that survival increased from 45 to 69% over the study period due to earlier diagnosis and treatment. 12 Babies with MAS requiring MV had the best outcome in Tortman H's study, 82% survived. 5 It is similar to our study.…”
Section: Resultsmentioning
confidence: 89%